2019
DOI: 10.1080/14606925.2019.1595855
|View full text |Cite
|
Sign up to set email alerts
|

Implementing design thinking as didactic method in entrepreneurship education. The importance of through

Abstract: Entrepreneurship has traditionally been taught about entrepreneurship. However, teaching entrepreneurship requires practice and learning by doing. Entrepreneurship education requires education through entrepreneurship where the students feel the real life of being an entrepreneur. The process of Design Thinking offers a method for teaching through entrepreneurship. This paper studies the didactic experiences from a course at Örebro University School of Business where entrepreneurship was taught using Design Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The body of knowledge relating to this sort of designer-led entrepreneurship has been slowly but steadily increasing, in the form of handbooks (Varon and Alberti, 2019;Talarico and Heller, 2016;Basadur and Goldsby, 2016), tools (Colombo et al, 2017), typologies (Valencia et al, 2018, Chen at al., 2018, case studies (Kremel and Edman, 2019;Valencia and Pearce, 2019;Val et al, 2019;Gaglione and Gaziulusoya, 2019;Liu and Rieple, 2019;Mata-Garcia, 2017Moller et al, 2013 and models (Mueller and Thoring, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The body of knowledge relating to this sort of designer-led entrepreneurship has been slowly but steadily increasing, in the form of handbooks (Varon and Alberti, 2019;Talarico and Heller, 2016;Basadur and Goldsby, 2016), tools (Colombo et al, 2017), typologies (Valencia et al, 2018, Chen at al., 2018, case studies (Kremel and Edman, 2019;Valencia and Pearce, 2019;Val et al, 2019;Gaglione and Gaziulusoya, 2019;Liu and Rieple, 2019;Mata-Garcia, 2017Moller et al, 2013 and models (Mueller and Thoring, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study aims to contribute to the current debate on the value of integrating Design Thinking into Entrepreneurship Education (Daniel et al, 2016;Huq & Gilbert, 2017;Linton & Klinton, 2019;Sarooghi et al, 2019;Val et al, 2019) by bringing convergence to a common understanding of the conceptualisation, practice and value of Design Thinking for Entrepreneurship Education to inform future Entrepreneurship Education practices. While previous research has quantified the wide use of Design Thinking within entrepreneurship curricula (Kremel & Edman, 2019;Sarooghi et al, 2019), this study sheds light on the quality of the Design Thinking integration in Entrepreneurship Education-from an educator's perspective. This study connects research on Design Thinking and Entrepreneurship Education with a particular focus on the Entrepreneurship Educator to examine -from an Educators point of view -the role and value Design Thinking may have in Entrepreneurship Education in the Higher Education context.Thus, to address the overarching aim, "What is the conceptual understanding, educational practice and perceived value of Design Thinking for entrepreneurship educators in Higher Education in UK & Northern Europe?"…”
Section: Research Aims and Objectivesmentioning
confidence: 94%
“…In 2020 the new Entre-Comp Playbook by the European Union was published, describing Design Thinking as one of the three most important entrepreneurial methods (Baciagalupo et al, 2020). Recent research has demonstrated the broad application of Design Thinking among Entrepreneurship Educators (Kremel & Edman, 2019) and confirmed that Design Thinking is integrated into more than half of the entrepreneurship curricula (54%) (Sarooghi et al, 2019).…”
Section: The Rationale For the Studymentioning
confidence: 98%
See 2 more Smart Citations